Exercise and heart failure. Relation of the severity of the disease to the anaerobic threshold and the respiratory compensation point - Guimarães,Guilherme Veiga (1999)
OBJECTIVE - To identify, the anaerobic threshold and respiratory compensation point in patients with heart failure. METHODS - The study comprised 42 Men,divided according to the functional class (FC) as follows: group I (GI) - 15 patients in FC I; group II (GII) - 15 patients in FC II; and group III (GIII) - 12 patients in FC III. Patients underwent a treadmill cardiopulmonary exercise test, where the expired gases were analyzed. RESULTS - The values for the heart rate (in bpm) at the anaerobic threshold were the following: GI, 122±27; GII, 117±17; GIII, 114±22. At the respiratory compensation point, the heart rates (in bpm) were as follows: GI, 145±33; GII, 133±14; GIII 123±22. The values for the heart rates at the respiratory compensation point in GI and GIII showed statistical difference. The values of oxygen consumption (VO2) at the anaerobic threshold were the following (in ml/kg/min): GI, 13.6±3.25; GII, 10.77±1.89; GIII, 8.7±1.44 and, at the respiratory compensation point, they were as follows: GI, 19.1±2.2; GII, 14.22±2.63; GIII, 10.27±1.85. CONCLUSION - Patients with stable functional class I, II, and III heart failure reached the anaerobic threshold and the respiratory compensation point at different levels of oxygen consumption and heart rate. The role played by these thresholds in physical activity for this group of patients needs to be better clarified.